Effects of Stearin and Lecithin Concentrations on Physical Properties of Chocolate - Misnawi Misnawi; Teguh Wahyudi (Indonesian Coffee and Cocoa Research Institute, 2008)
Herbal coffee is one of the coffee diversivication product that has been well recognized in the market. The addition of herbs or spices, such as ginger, pasak bumi (Eurycoma longifolia), Panax (from the genus of Panax L.) and Habbatussauda (black cumin/black seed/Nigella sativa) in the coffee, not only offer an enhanced flavor characteristic, but more importantly also offer the consumer to gain a health benefit which are possessed by the herbs used. Cardamom (Amonum cardomum) is commonly recognized as a food spices to add flavor to dishes. Cardamom is also known as a herb that possess health benefit such as the medicine for tonsil and throat inflammation, fever, asthma and fatigue reliever. This research was aimed to develop a herbal coffee containing the extract of cardamom and to study the characteristic of herbal coffee obtained physicochemically and by sensory analysis. Crystallized coffee and sugar mixture was blended with cardamom extract by several ratio, which were 90%:10%, 80%:20%, 70%:30%, 60%:40% and 50%:50% to obtain ready to drink cardamom herbal coffee. The mixtures and control (without the addition of cardamom) were then subjected for consumer perception by testing it to 30 panelist based on hedonic sensory test. The 3 mixtures that were choosen were then analysed for its physicochemical characteristic such as its powder and brewing appearrance, insoluble solids, reducing sugar and caffein concentration. The result showed that the addition of 10%, 20% and 30% cardamom extracthad good preferences to consumer, which 10% of addition resulted the highest preferences. The hedonic sensory test resulted the preferences of the aforementioned herbal coffee on color, aroma, taste and flavor was 3.37; 3.14; 3.30; 3.27 and 3.37 (on scale 1 to 5), respectively, representing moderately like to like preferences.The physiscochemical analysis show that the mixture contain 0.17% of insoluble solid, 0.13% of reducing sugar and 0.45% caffeine which comply the Indonesia standard of SNI 4446:1998. This result show that the cardamom herbal coffee is potential to be developed as on of coffee diversification product. Keywords: coffee mix, herbal, cardamom, coffee diversification.